Morphometric Analysis and Growth Patterns of Blood Cockle (Tegillarca granosa) in Langsa Mangrove Ecosystems, Indonesia - Mawardi, Mawardi; Sarong, M. Ali; Suhendrayatna, Suhendrayatna; Irham, Muhammad (Grimsa Journal of Science Engineering and Technology, 2024)
The mangrove area is a nutrient-rich zone that serves as a food source for various aquatic organisms and as a spawning and nursery ground for species such as fish, crabs, and clams. The aim of this study is to investigate the morphometrics and growth pattern of blood cockle (Tegillarca granosa) in the mangrove area of Langsa City. Data collection for T. granosa was conducted using purposive sampling at three designated research locations with varying environmental conditions. Transects were established from the shoreline towards the mangrove vegetation at each research location. Within each transect, 1 meter x 1 meter plots were established for T. granosa sampling. The blood cockles found at the research sites were measured for shell length, shell width, and total weight. The research collected 98 individuals of T. granosa at the study location, with morphological variations including length, width, total weight, and sex. The size of the blood cockles ranged from 3 cm to 6.76 cm, the shell width ranged from T. granosa 2.50 cm to 5.52 cm, while the total weight of T. granosa ranged from 12 grams to 122 grams. Based on morphometric analysis, the growth pattern of T. granosa in the mangrove area of Langsa City is characterized by b = 2.5085, falling into the negative allometric category. This growth pattern indicates that the length of T. granosa grows faster compared to its total weight. Location 1 (Lhok Banie) showed the best growth pattern for T. granosa, the least favorable growth was found at Location 3 (Kuala Langsa). In conclusion, the morphometrics of T. granosa at the study site showed significant variation in length, width, and total weight. Morphometric analysis indicates that T. granosa exhibits a negative allometric growth pattern.